2006
DOI: 10.1038/sj.bjc.6602909
|View full text |Cite
|
Sign up to set email alerts
|

SCOTROC 2A: Carboplatin followed by docetaxel or docetaxel–gemcitabine as first-line chemotherapy for ovarian cancer

Abstract: The feasibility of sequential carboplatin followed by docetaxel-based therapy for untreated ovarian cancer was determined. Patients received four q3w cycles of carboplatin AUC 7, then four q3w cycles of either docetaxel 100 mg m À2 (day 1) (arm A); docetaxel 75 mg m À2 (day 8) and gemcitabine 1250 mg m À2 (days 1,8) (arm B) or docetaxel 25 mg m À2 and gemcitabine 800 mg m À2 (both given weekly (days 1,8,15)) (arm C). A total of 44 patients were randomised to each treatment arm. None of the arms demonstrated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
6
0
2
Order By: Relevance
“…We were interested to read a recent article by Vasey et al (2006) in which the authors expressed some concern about the incidence of pulmonary toxicity (Ptox) in patients treated with a taxanegemcitabine regimen, an issue that has been raised by several others (Thomas et al, 2000;Bhatia et al, 2002;Harries et al, 2004). The rare specific adverse drug reactions (ADRs) classified as Ptox are known to occur with the use of gemcitabine (Gem) and both taxanes, docetaxel (Doc) and paclitaxel (Pac).…”
Section: Sirmentioning
confidence: 99%
“…We were interested to read a recent article by Vasey et al (2006) in which the authors expressed some concern about the incidence of pulmonary toxicity (Ptox) in patients treated with a taxanegemcitabine regimen, an issue that has been raised by several others (Thomas et al, 2000;Bhatia et al, 2002;Harries et al, 2004). The rare specific adverse drug reactions (ADRs) classified as Ptox are known to occur with the use of gemcitabine (Gem) and both taxanes, docetaxel (Doc) and paclitaxel (Pac).…”
Section: Sirmentioning
confidence: 99%
“…Our results show that G/D therapy has a serious risk of pulmonary toxicity in line with others [4][5][6]. Possibly, gemcitabine-induced cytokine release can potentiate the lung toxicity of docetaxel, however, docetaxel might also augment gemcitabine-induced cytokine release.…”
Section: Discussionmentioning
confidence: 47%
“…There was no pulmonary toxicity in this study in contrast to the experience of Harries et al (25) with a similar protocol but with paclitaxel on days 1, 8, and 15 during which several patients experienced breathlessness, interstitial lung changes, and decreased diffusing capacity [DLCO (diffusion capacity of the lung for carbon monoxide)]. Vasey et al (26) also reported significant pulmonary toxicity with a similar study of carboplatin followed by docetaxel and gemcitabine on days 1, 8, and 15. The weekly schedule appears to be related to pulmonary toxicity and should be avoided.…”
Section: Discussionmentioning
confidence: 50%